THE DIALECTICS OF ENGLISH DOMINANCE - MONZO, LILIA D. (Society Register, 2020)
The Hegemony of English across the world cannot be overstated (Macedo, Dendrinos & Gounari 2016). More and more nations are encouraging, if not mandating through compulsory education requirements, that their citizens learn English (Xue & Zuo 2013). This demand for English is rising even among countries who have few native speakers of English. Importantly, making any language learning a national project carries a critical message about that language and its power. Robert Philipson (2011) points out that this growing demand and compulsory establishment of English (through schooling) can be nothing less than linguistic imperialism, with the World Bank re-introducing the historical colonial order. Nations are clamoring to learn English as quickly as possible in the hopes that doing so will boost their competitive edge on the global market (McCormick 2013). Indeed, there is evidence that English proficiency elevates the status and power of specific nations and provides individuals greater access to jobs and resources, but as Anna Odrowaz-Coates shows, in the case of Portugal and Poland, this will not happen without a significant cost to the national identity and to the identities of the people and their families and communities.